Rotational double-beam piezoelectric energy harvester impacting against a stop. (17th March 2020) - Machado, S.P.; Febbo, M.; Ramírez, J.M.; Gatti, C.D.
Abstract: In this paper, a low-frequency rotational piezoelectric energy harvester is proposed to operate out of resonance with the incorporation of a flexible stop. A numerical scheme is developed for the analysis of the contact problem of a harvester system impacting against a stop. The device consists of two flexible beams, two heavy masses joined by a linear spring and a single side spring stop. The purpose of the flexible stop is to limit the maximum displacement to preserve the structural integrity of the beams and to increase the harvested power in a low frequency range of operation (0.7–2.5 Hz). The rotational energy harvesting (REH) system vibrates at the frequency of the gravitational force, which acts as a periodic source and causes voltage generation by virtue of the piezoelectric effect. Contrary to what happens in most impact problems where the contact force increases with the acceleration of the base, in our prototype the contact force is maximum at the lowest rotation frequency. This feature makes it novel because it is proposed as an alternative solution for the problem of low energy generation at a very low excitation frequency. The prototype energy harvester, which is designed to provide energy to wireless autonomous monitoring systems in wind turbines of 30 KW with rotational speeds between 50–150 rpm, generates a rectified power of 102–845 μW. The efficiency of mechanical to electrical conversion for the prototype is about 80%. Graphical abstract: Image 1 Highlights: A flexible stop limits the response of a rotational energy harvester. An appropriate numerical scheme calculates the contact force. The role of the centrifugal force is fundamental as design element in the dynamics. The contact force is maximum at the lowest rotation frequency. The harvest of DC power for 0.7–1.3 Hz is between 102 and 845 μW.